How Foliar Fungal Diseases Affect Nitrogen Dynamics, Milling, and End-Use Quality of Wheat - Simón, María Rosa; Fleitas, María Constanza; Castro, Ana Carolina; Schierenbeck, Matías (Frontiers in Plant Science, 2020)
Foliar fungal diseases affect yield and quality of bread wheat (Triticum aestivum L.) causing important losses. They may impact differently on crop growth-rate, modifying nitrogen (N) dynamics and carbohydrate accumulation in the grain. The relationship between N and carbohydrates accumulation determines the grain protein concentration which impacts on the gluten concentration and rheological properties of the wheat flour. In addition, types of fungicides and N fertilization can influence the intensity of foliar diseases and have an effect on the milling and end-use quality, depending on the bread-making aptitude of the genotypes, the nutritional habit of the pathogens involved the amount and time of the infections, environmental factors and interactions between these factors. In that way, N fertilization may increase or decrease the severity of the diseases depending on the nutritional habit of the pathogen. Some fungicides, such as strobilurins and carboxamides, produce high levels of disease control, and prolong the healthy leaf area duration which translates into important yield responses potentially compromising the grain protein concentration by additional carbohydrate production with consequences in the bread-making quality. Furthermore, infections caused by biotrophic pathogens can be more detrimental to N accumulation than to dry matter deposition, whereas the reverse has been generally true for diseases caused by necrotrophic pathogens. The time of infection could also affect yield components and N dynamics differentially. Early epidemics may reduce the number of grains per area and the N remobilization, whereas late epidemics may affect the thousand kernel weight and mainly the N absorption post-flowering. A review updating findings of the effects of infections caused by foliar fungal pathogens of different nutritional habits and the incidence of several factors modifying these effects on the above-ground biomass generation, N dynamics, protein and gluten concentration, milling, rheological properties, loaf volume and other quality-related trait is summarized. Three main pathogens were especially taken as representative of biotrophic (Puccinia triticina), necrotrophic (Pyrenophora tritici-repentis) and hemibiotrophic (Zymoseptoria tritici) nutritional habit, as recent information is available and some general models of their effects are proposed. New challenges for researchers to minimize the impact of foliar diseases on end-use quality are also discussed.